Reformasi Politik, Demokrasi, dan Integrasi Nasional - J. Nasikun (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
The multifacet and multilayers of crisis that Indonesia has been suffering from requires a deep reflection on how it come about and a fundamental transformation. This article attempts to offer a reflective account on what had been happening in Indonesia, especially during the New Order rule which lead to institutionalization of state corporatism and democratic royalism, romanization of national law dan the death of political community. despute the depth of the crisis, this article attemps to resque an optimism for engaging in a long process of political reform, democritizing and maintaining national integration through a cereful management of pluralism, localism and the sense of community.